Acoustic wave propagation in anisotropic media with applications to piezoelectric materials. Issue 3 (11th February 2022) - Stachura, Eric
ABSTRACT: In this paper, we analyze acoustic wave propagation in anisotropic fluids and solids. By formulating the acoustic system as an evolution equation over a Hilbert space, we obtain global in time solutions when the associated material parameters are bounded and measurable. In particular, we prove well-posedness of a Cauchy problem for wave propagation in piezoelectric crystals. We then provide a stability analysis of these solutions not assuming positive definiteness of the stress–strain tensor or the piezoelectric stress tensor. Finally we prove continuous dependence on initial data, allowing the piezoelectric tensor to depend on space and time, provided solutions belong to an appropriate function space.